PENGARUH PROMOSI DAN BRAND IMAGE TERHADAP MINAT BELI KONSUMEN PADA PLATFORM SHOPEE (STUDI KASUS MAHASISWA FEB UNIK) - Elly Anugrah Utami; Yudiarto Perdana Putra (Jurnal Gici Jurnal Keuangan dan Bisnis, 2025)
Purchasing products online is very easy through an online shop, namely Shopee. Shopee is one of the leading e-commerce in Indonesia. Since its launch until now, Shopee's basic services can be used by everyone for free. As one of the most visited marketplaces, Shopee provides a variety of complete offers. The ease of online shopping has many factors that can influence purchasing interest. This study aims to determine the effect of Promotion and Brand Image on Consumer Purchase Interest on the Shopee platform for FE University of Kadiri students. This type of research is quantitative and tests hypotheses to explain the relationship between variables. 90 respondents are the sample of this study. The purposive sampling and snowball sampling methods were used to distribute questionnaires to students of the Faculty of Economics majoring in S1 Management, University of Kadiri, who have Shopee e-commerce applications and have made purchases / transactions. Researchers use multiple linear regression analysis. The test results show partially and simultaneously that promotion and brand image have a positive and significant effect on purchasing interest.